UNCOVERING THE EXPERIENCES AND CHALLENGES OF EFL LEARNERS IN MBKM PROGRAM - Alfian, Alfian; Trimadona, Eliza; Noprival, Noprival; Berliana, Idea (STKIP Siliwangi, 2025)
Despite existing research on the implementation of the Independent learning- independent campus (MBKM) program, limited attention has been given to the experiences of EFL learners participating in the student exchange and entrepreneurship programs. To fill this gap, this study aims to explore the perceptions and experiences of EFL learners participating in the MBKM program. Utilizing a case study design, data were gathered from four EFL learners at a university in Indonesia. Interviews were conducted, and the data were analyzed using thematic analysis aided by computer-assisted qualitative data analysis software (CAQDAS), MAXQDA. The findings reveal that the EFL learners exhibited a highly positive attitude toward the program. The findings also indicated that the EFL learners perceive the MBKM program favorably due to its diverse benefits, including opportunities to study at other universities and entrepreneurship skill development. Challenges identified include issues related to fund distribution from the government, as well as culture shock and homesickness. This study informs policy and practice to enhance support for MBKM participation and maximize its benefits.